Tradisi Mengantarkan Siunjuik pada Acara Baralek di Nagari Sariak Laweh Kabupaten Limapuluh Kota Menurut Urf - Afifah Farah; Rahmiati (AHKAM, 2026)
The tradition of delivering siunjuik during a baralek ceremony in Nagari Sariak Laweh, Lima Puluh Kota Regency, is a custom passed down through generations and performed by the husband’s bako family as a form of responsibility toward the newlyweds. However, this tradition is also regarded as a customary obligation that may impose an economic burden on some members of the community. This study aimed to describe the implementation of the tradition of delivering siunjuik and analyze it from the perspective of ‘urf in Islamic law. The study employed a qualitative approach with a field research design. Primary data were obtained through in-depth interviews with customary leaders, penghulu, ninik mamak, Bundo Kanduang, pangka tuo, and community members, whereas secondary data were derived from books, journals, previous studies, and supporting documents. Data were collected through interviews and documentation and were subsequently analyzed descriptively and inductively. The results showed that the tradition of delivering siunjuik was performed at night during the baralek ceremony by bringing various items needed by the newlyweds as a symbol of the bako family’s responsibility. This tradition embodies the values of togetherness, responsibility, and the strengthening of kinship ties. However, increasing standards regarding the items provided during its implementation have imposed an economic burden on some members of the community. From the perspective of ‘urf, the tradition of delivering siunjuik is classified as ‘urf shahih because it does not conflict with Islamic law and provides benefits. This study contributes to the development of studies on Islamic law and Minangkabau customs and provides practical implications for customary leaders and the community to preserve the tradition while considering the principles of ease and economic capacity so that its implementation remains consistent with Islamic values.